2010
DOI: 10.1080/08897070903442699
|View full text |Cite
|
Sign up to set email alerts
|

How is Substance Use Linked to Psychosis? A Study of the Course and Patterns of Substance Dependence in Psychosis

Abstract: Substance use in mentally ill patients is now a major problem that influences the course and outcome of psychosis. With prevalence ranging up to 60%, several theories were postulated to explain the link. It would be interesting to know if substances have different effects in persons with psychosis than in those without. This study aimed to explore patterns of symptomatology of dependence and comorbid psychiatric illness by comparing and contrasting it with a group suffering from pure substance dependence. Cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(30 citation statements)
references
References 64 publications
0
29
0
1
Order By: Relevance
“…6 Cannabis, alcohol and nicotine are the most commonly used substances globally, and there is often polysubstance use in patients with mental illness and particularly psychosis. 7 Cannabis use is also associated with various other non-psychotic mental illnesses in adolescents, including conduct disorders, attention deficit hyperactivity disorder (ADHD), depression and suicidal behaviour. 8 For example, in a review of 236 adolescent psychiatric patients in Israel, the most common diagnoses among cannabis users were ADHD and disruptive behaviour disorder.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…6 Cannabis, alcohol and nicotine are the most commonly used substances globally, and there is often polysubstance use in patients with mental illness and particularly psychosis. 7 Cannabis use is also associated with various other non-psychotic mental illnesses in adolescents, including conduct disorders, attention deficit hyperactivity disorder (ADHD), depression and suicidal behaviour. 8 For example, in a review of 236 adolescent psychiatric patients in Israel, the most common diagnoses among cannabis users were ADHD and disruptive behaviour disorder.…”
Section: Introductionmentioning
confidence: 99%
“…11 Studies have also reported that adult patients with psychosis have a different pattern of substance use with earlier tolerance, loss of control and onset of dependence. 7 This has not been investigated in exclusive adolescent samples.…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, early onset of cannabis use and at least weekly cannabis use during adolescence have been identified as risk factors for problems later in life. For instance, cannabis use in this age period may impair educational performance, may cause respiratory disease in the long term and increases the probability of developing psychotic symptoms [1][2][3][4][5][6]. Besides these adverse outcomes, it has been estimated that one in seven adolescents who have ever tried cannabis will experience dependency problems during their life-time [7].…”
Section: Introductionmentioning
confidence: 99%
“…Ceci s'explique fort probablement par le fait qu'elles sont plus isolées, moins souvent en couple et que peu d'entre elles ont des enfants. À l'inverse, ces personnes mentionnent des difficultés plus notables sur le plan de la consommation de drogues dures et douces, possiblement dans une optique d'automédication (Saddichha, Sur, Sinha et Khess, 2010). En effet, il est reconnu que l'observance à la médication constitue un enjeu majeur pour les personnes souffrant de troubles psychotiques (Joy, Adams et Rice, 2006).…”
Section: Discussionunclassified